2005
DOI: 10.1038/sj.bjp.0706169
|View full text |Cite
|
Sign up to set email alerts
|

The role of joint nerves and mast cells in the alteration of vasoactive intestinal peptide (VIP) sensitivity during inflammation progression in rats

Abstract: 1 The present study examined the peripheral effects of vasoactive intestinal peptide (VIP) on rat knee joint blood flow during acute and chronic inflammation. The involvement of joint nerves and synovial mast cells on these effects was also investigated. 2 Prior to blood flow assessment, animals were deeply anaesthetised with ethyl carbamate (urethane; 2 mg kg À1 i.p.). Local application of VIP (10 À13 -10 À9 mol) onto the capsular surface of normal rat knee joints caused a dose-dependent increase in synovial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
0
14
1
Order By: Relevance
“…PAC1 receptors have been described mainly on neurons and smooth muscle cells (Ekblad 1999;Hernandez et al 2004). VPAC1/VPAC2 receptors are expressed in the dorsal horn of the spinal cord, on knee joint afferents, inflammatory and immune cells including mast cells and fibroblast-like synoviocytes (McDougall and Barin 2005;Takeba et al 1999). All the known receptors for PACAP are coupled to adenylate cyclase activation and therefore increase cAMP concentration, stimulate phospholipase C leading to inositol trisphosphate (IP 3 )-mediated Ca 2+ mobilization, and activate Ca 2+ -and diacylglycerol-dependent protein kinase C or stimulate NO synthesis (Lutz et al 2006;Shioda et al 2006;Vaudry et al 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…PAC1 receptors have been described mainly on neurons and smooth muscle cells (Ekblad 1999;Hernandez et al 2004). VPAC1/VPAC2 receptors are expressed in the dorsal horn of the spinal cord, on knee joint afferents, inflammatory and immune cells including mast cells and fibroblast-like synoviocytes (McDougall and Barin 2005;Takeba et al 1999). All the known receptors for PACAP are coupled to adenylate cyclase activation and therefore increase cAMP concentration, stimulate phospholipase C leading to inositol trisphosphate (IP 3 )-mediated Ca 2+ mobilization, and activate Ca 2+ -and diacylglycerol-dependent protein kinase C or stimulate NO synthesis (Lutz et al 2006;Shioda et al 2006;Vaudry et al 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids are able to inhibit noradrenaline release from postganglionic sympathetic efferents ( Ishac et al , 1996 ; Varga et al , 1996 ; Niederhoffer and Szabo, 1999 ), thereby attenuating sympathetic vascular tone and leading to hyperaemia. Articular blood vessels are also innervated by sensory nerves containing vasoactive neurotransmitters, such as substance P, vasoactive intestinal peptide and calcitonin gene‐related peptide ( Bjurholm et al , 1990 ; Abramovici et al , 1991 ; McDougall et al , 1997 ), all of which have been shown to increase synovial blood flow ( Lam and Ferrell, 1993 ; McDougall et al , 1995 , 1999 ; McDougall and Barin, 2005 ). These neuropeptides are released from vasosensory nerves in response to activation of the capsaicin‐sensitive TRPV1 channel.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this inability of JWH133 to elicit a hyperaemic response in arthritic knees could be that the synovial microvasculature is already maximally vasodilated such that supplementary smooth muscle relaxation is unattainable in these models. Studies testing other vasodilators in these same inflammatory models, however, have successfully demonstrated that arthritic joint blood vessels possess a vasodilator reserve, indicating that vascular smooth muscle relaxation is still possible in these joints ( McDougall and Barin, 2005 ; Zhang and McDougall, 2006 ). An alternative reason for the lack of a vasodilatatory response to JWH133 in arthritic knees is that there could be an alteration in articular CB 2 receptor expression and/or sensitivity in inflamed joints; however, this possibility requires further experimental assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory neurogenic molecules that have received the most attention have been the neuropeptides substance P (SP), calcitonin gene related peptide (CGRP) and vasoactive intestinal peptide (VIP). These peptides are capable of increasing synovial blood flow [31,32], protein extravasation [33], leukocyte recruitment [34] and pain [35]. Exogenously administered VIP, for example, increases nociceptor activity and joint pain, while VIP antagonism is analgesic in OA joints [36,37].…”
Section: Neuropeptidesmentioning
confidence: 99%